2023
DOI: 10.1111/ppl.13945
|View full text |Cite
|
Sign up to set email alerts
|

The emerging key role of reactive sulfur species in abiotic stress tolerance in plants

Abstract: In plants, sulfur plays a critical role in the formation of important biomolecules such as cysteine, methionine, and tripeptide glutathione. Thiol groups, composed of sulfur, are essential to numerous metabolic processes. The easy and reversible oxidation and reduction of thiol groups have drawn attention to the redox regulation of cellular metabolism. Reactive sulfur species (RSS), including hydrogen sulfide (H 2 S), persulfides, and polysulfides, are synthetized in all living organisms, mainly from cysteine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 124 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…AA or NO potentially stimulated cysteine production whatever the treatment used, thus, the whole sulfur pool was sufficiently stimulated to cope with the toxic Li 2 or combined stressors. It has been reported that the interaction of GSH and GSTs modifies cellular detoxification by a wide variety of electrophilic compounds in cells because of their affinity to deregulated xenobiotics [ 112 ]. Unlike the other GSH-related compounds, the activity of GST increased highly significantly for Li 2 and the combined stressors.…”
Section: Discussionmentioning
confidence: 99%
“…AA or NO potentially stimulated cysteine production whatever the treatment used, thus, the whole sulfur pool was sufficiently stimulated to cope with the toxic Li 2 or combined stressors. It has been reported that the interaction of GSH and GSTs modifies cellular detoxification by a wide variety of electrophilic compounds in cells because of their affinity to deregulated xenobiotics [ 112 ]. Unlike the other GSH-related compounds, the activity of GST increased highly significantly for Li 2 and the combined stressors.…”
Section: Discussionmentioning
confidence: 99%
“…The examination of trait variations in plants under stress situations is an important area in plant ecology and environmental biology [24]. Stressors encompass biological stresses (e.g., pathogen infection), physical stresses (e.g., heat, drought, and salinity), and chemical stresses (e.g., soil contamination) [25][26][27], which may induce a range of physiological, morphological, and molecular trait changes in plants.…”
Section: Introductionmentioning
confidence: 99%